1970
DOI: 10.1002/qua.560040302
|View full text |Cite
|
Sign up to set email alerts
|

A study of the ground state wave function of carbon monoxide

Abstract: AbstractsA large configuration-interaction calculation has been performed to determine the wave function, energy, and molecular properties of CO. The most important configurations were used to obtain the natural geminals and their occupation numbers. A pair-energy approach to the correlation energy was attempted with results which differ significantly from the configuration-interaction results.On a fait un calcul CI avec un grand nombre de configurations, pour CO pour dCterminer la fonction d'onde, 1'Cnergie e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…It has been argued that strong orthogonality is too severe of an approximation. 4,13,47 We think that some deficiencies associated with strongly orthogonal geminals were due to the incomplete optimization of the geminal wave function in earlier studies. 15 The best way to evaluate the quality of approximations used in the SSG model is, in our view, to examine all perturbative corrections.…”
Section: Quality Of Ssg Reference Wave Functionmentioning
confidence: 99%
“…It has been argued that strong orthogonality is too severe of an approximation. 4,13,47 We think that some deficiencies associated with strongly orthogonal geminals were due to the incomplete optimization of the geminal wave function in earlier studies. 15 The best way to evaluate the quality of approximations used in the SSG model is, in our view, to examine all perturbative corrections.…”
Section: Quality Of Ssg Reference Wave Functionmentioning
confidence: 99%
“…The pair energies resulting from the two-body perturbation calculations are compared with the pair-excitation energies obtained by the method of configuration interaction [7] in Table IV. In all three calculations, the matrix …”
Section: Comparison Of Pair Energies With Configuration Interactionmentioning
confidence: 99%
“…The present study represents one of the first applications of the third-order many-body perturbation expansion for a molecule not containing a hydrogen atom, and it does permit some comparison with configuration interaction. Although the configuration interaction calculation reported by Siu and Davidson [7] employs a larger basis set, and includes single-excitations which third-order MBPT does not, a comparison between the two results is nevertheless useful. A comparison of two-body perturbative and certain pair-restricted configuration interaction calculations [2,7] is presented first.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we can be quite confident that the energy lowering from the SCF observed in the subsequent calculations is predominantly a correlation effect. Since our basis set is much less flexible than the one used in the recent iterative natural orbital CI calculation of Siu and Davidson [8], we cannot hope to recover as high a percentage of the total correlation energy as these authors. Previous calculations [ 1, 31 have shown that the basis set limit for the type of basis used in this work is about 50% of the correlation energy of the valence shell.…”
Section: Ds-asepc + Bclc2mentioning
confidence: 99%